10 UX principles every developer must know (O'Reilly Media, 2019)
"Josh Clark and Mike Biglan (Twenty Ideas) give you some tools to use so that you, as a developer, can be a UX beast. They explore how to nurture curiosity as a means of understanding the user; how to leverage psychology, including decision science, in the process of developing workflows; how to communicate and argue well; and how to become a UX developer unicorn--winning friends and influencing people (including your boss) to become a more valuable and critical member of any team. This session was recorded at the 2019 O'Reilly Open Source Software conference in Portland."--Resource description page